RNA Demethylase ALKBH5 Prevents Lung Cancer Progression by Regulating EMT and Stemness via Regulating p53 - Liu, Xiangli; Wang, Ziyi; Yang, Qiwei; Hu, Xiaohai; Fu, Qiang; Zhang, Xinyu; Li, Wenya (Frontiers in Oncology, 2022)
Background Although N6-methyladenosine (m6A) RNA methylation is the most abundant reversible methylation of mRNA, which plays a critical role in regulating cancer processing, few studies have examined the role of m6A in nonsmall-cell lung cancer-derived cancer stem-like cells (CSCs). Methods CSCs were enriched by culturing NSCLC cells in a serum-free medium, and stem factors, including CD24, CD44, ALDH1, Nanog, Oct4, and Sox2 were detected by Western blot. ALKBH5 expression was measured by employing a tissue array. Global m6A methylation was measured after ALKBH5 knockdown. Malignances of CSCs were detected by performing CCK-8 assay, invasion assay, cell cycle analysis, and tumor formation in vitro and in vivo. Results m6A demethylase ALKBH5 is highly expressed in CSCs derived from NSCLC. Knockdown of ALKBH5 increased global m6A level, and also increased E-cadherin, decreased stem hallmarkers, Nanog and Oct4, and inhibited stemness of CSCs. In lung carcinoma, ALKBH5 is found to be positively correlated with p53 by using Gene Expression Profiling Interactive Analysis (GEPIA) online tool. P53 transcriptionally regulates ALKBH5 and subsequently regulates the global m6A methylation level. Knockdown of p53 or inhibition of p53’s transcriptional activity by addition of its specific inhibitor PFT-α decreased expression of ALKBH5 and CSCs’ malignancies, including proliferation, invasion, and tumor formation ability, indicating that p53 may partially regulate CSC’s malignancies via ALKBH5. Furthermore, we also found p53 transcriptionally regulates PRRX1, which is consistent with our previous report. Conclusion Collectively, our findings indicate the pivotal role of ALKBH5 in CSCs derived from NSCLC and highlight the regulatory function of the p53/ALKBH5 axis in modulating CSC progression, which could be a promising therapeutic target for NSCLC.